2019
DOI: 10.1038/s41560-019-0327-0
|View full text |Cite
|
Sign up to set email alerts
|

Net energy analysis must not compare apples and oranges

Abstract: Energy return on investment (EROI) is a critical measure of the comparative utility of different energy carriers including fossil fuels and renewables. However it must not be used to compare carriers that cannot be put to similar end-use. Additionally, combining carriers to arrive at estimates of 'average' or 'minimum' EROIs can be problematic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 20 publications
0
50
0
1
Order By: Relevance
“…Assessing rapeseed production for biodiesel in Europe van Duren et al (2015) concluded that the maximum gross EROI was 2.2:1. Though further work is required to align all studies system boundaries, ensuring no overestimations and no 'apples-tooranges' comparisons (Murphy et al 2016;Raugei 2019), these estimates evidence the limited capacity of biofuel production to maintain a sufficient net energy supply to society.…”
Section: Is Global Aaff Approaching Biophysical Limits?mentioning
confidence: 98%
“…Assessing rapeseed production for biodiesel in Europe van Duren et al (2015) concluded that the maximum gross EROI was 2.2:1. Though further work is required to align all studies system boundaries, ensuring no overestimations and no 'apples-tooranges' comparisons (Murphy et al 2016;Raugei 2019), these estimates evidence the limited capacity of biofuel production to maintain a sufficient net energy supply to society.…”
Section: Is Global Aaff Approaching Biophysical Limits?mentioning
confidence: 98%
“…However, the NEA literature has historically been characterized by a much lower degree of standardization than the LCA one, which has led to many inconsistent comparisons [71,72].…”
Section: Net Energy Analysis (Nea)mentioning
confidence: 99%
“…Although there are standards recommending methods to compile energy statistics [29], conflicting approaches remain between major groups in the calculation of the contribution to global primary energy from non-thermal electricity sources such as from hydro, wind and photovoltaic (PV) cells [11], see Table 1. These conflicts are inevitable, given that as Raugei [30] has pointed out comparing electricity and thermal energy is like counting 'apples and oranges' together. The IEA [2] method converts primary electricity to primary energy on a 1:1 basis, although for all thermal sources of electricity, whether FF, RE, or nuclear, the input heat energy is used based on a conversion efficiency of 33%.…”
Section: Treatment Of Primary Re Electricitymentioning
confidence: 99%